2011
DOI: 10.1186/1746-1596-6-106
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial outbreak of imipenem-resistant Pseudomonas aeruginosa producing VIM-2 metallo-β-lactamase in a kidney transplantation unit

Abstract: BackgroundTwenty four non replicate imipenem resistant P. aeruginosa were isolated between January and November 2008, in the kidney transplantation unit of Charles Nicolle Hospital of Tunis (Tunisia). This study was conducted in order to establish epidemiological relationship among them and to identify the enzymatic mechanism involved in imipenem resistance.MethodsAnalysis included antimicrobial susceptibility profile, phenotypic (imipenem-EDTA synergy test) and genotypic detection of metallo-β-lactamase (MBL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 35 publications
3
36
1
Order By: Relevance
“…According to the literature, colonization and infection by multidrug-resistant bacteria, especially Pseudomonas and Acinetobacter, is an important and predictive factor for intra-hospital patient death, mainly of immunocompromised individuals [14,34,35]. Our results corroborate data in the literature; high mortality was observed among patients from whom multidrugresistant P. aeruginosa and Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…According to the literature, colonization and infection by multidrug-resistant bacteria, especially Pseudomonas and Acinetobacter, is an important and predictive factor for intra-hospital patient death, mainly of immunocompromised individuals [14,34,35]. Our results corroborate data in the literature; high mortality was observed among patients from whom multidrugresistant P. aeruginosa and Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 82%
“…Considering P. aeruginosa, as the isolation of carbapenem-resistant strains has been growing increasingly in Brazilian hospitals, literature data corroborate our findings that resistance was observed against piperacillin-tazobactam, ceftazidime, cefepime, aztreonam, and ciprofloxacin, but no resistance was observed against polymyxin B [6,8,34,37]. In this context, our results may support, on a regional scale, the reports by the SENTRY program, which pointed out polymyxin B as an alternative drug against multidrugresistant P. aeruginosa [40].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Sixty percent of the isolates carried identical bla VIM sequences (which, based on the amplicon sequence, were consistent with bla VIM-2 or four other, less frequently observed variants: bla VIM-10 , bla , bla , and bla VIM-30 ), and 40% of the isolates were found to contain bla DIM-1 . While bla VIM (and especially bla VIM-2 ) is acknowledged as one of the most commonly isolated MBLs in Africa and throughout the world (19)(20)(21)(22), the presence of bla DIM-1 has been reported only once before, for a Pseudomonas stutzeri isolate from The Netherlands (23). In this study, bla DIM-1 was found in hospital isolates belonging to the families Enterobacteriaceae, Pseudomonadaceae, Burkholderiaceae, and Comamonadaceae.…”
mentioning
confidence: 68%
“…P. aeruginosa populations undergo frequent recombination events contributing to the evolution of successful epidemic clones [6]. These populations are dominated by common clones that can be isolated from diverse clinical and environmental sources [7].…”
Section: Introductionmentioning
confidence: 99%